Rediscovery and reinstatement of Heracleum amanum (Apiaceae) based on morphological and carpological data - Guzel, Yelda; Kayikçi, Samim (Phytotaxa, 2017)
Heracleum amanum was only known so far from the material collected in the Amanos Mountains, near Belen (southern Turkey) in 1862 by C.G.T. Kotschy, which was referred to in the protologue. This taxon was considered a mere variant of H. crenatifolium in Flora of Turkey, and apparently it had never been collected again. In the present contribution, the rediscovery of H. amanum is reported about 150 years after the first publication of the name, and recent gatherings are compared to samples of H. crenatifolium on the basis of carpological and morphological data. As a result of the investigations carried out, H. amanum and H. crenatifolium are suggested here to be treated as separate species, both endemic to Turkey. Distribution and habitat data, as well as their conservation status, are assessed for each one.